Oil spill clean-up using immersed metal wool. Issue 5 (October 2017) - Sezer, Hayri; Arsava, Kemal S.; Rangwala, Ali S.
Abstract: This study analyzes the burning behavior of a fuel immersed in porous metal wool with the ultimate goal of designing a method for faster cleanup of hazardous spills on water. The experiment comprises of burning a thin layer of fuel (dodecane) floating on water with the presence of metal-wool immersed inside the fuel layer. As the fuel burns, the metal wool heats up and consequently enhances the fuel vaporization rate. Different metal-wool thicknesses are used to investigate its impact on the burning rate. The experiments are used to validate a numerical model, which is then used to perform a parametric study. The predicted temperature transients and mass loss rate show good agreement with the experimental results. The simulation results indicate that the optimum metal wool thickness is a function of effective nucleation area.